ECB asset purchases may affect wealth distribution - Kerstin Bernoth; Philipp König; Benjamin Beckers (DIW Economic Bulletin, 2016)
In the debate on monetary policy decisions, to date, little attention has been paid to distributional effects. One reason for this is that they are not included in the mandate of the European Central Bank (ECB). Given the loose monetary policy stance in the euro area and the large-scale program to purchase government and corporate bonds launched in January 2015, the question increasingly being asked is whether any distributional effects can be ignored any longer. The present report looks at the channels of monetary policy that are potentially relevant to distribution and conducts an initial assessment of their relevance to asset purchases in the euro area. The asset purchase program has probably led to rising asset prices, thereby mainly benefitting households at the upper end of the wealth distribution. This is likely to lead to a direct increase in wealth inequality. Whether or not this increase can be at least partially offset in the long term is uncertain. Indebted and/or low-income households could benefit if the program contributes successfully to economic recovery and higher inflation, and therefore helps to improve employment opportunities. So far, the overall distributional effect is therefore unclear. A more in-depth analysis is required in the future.
Keywords: D31; E52; E58; 330; large-scale asset purchases; wealth inequality; monetary policy; zero-lower bound